High-throughput label-free detection of Ochratoxin A in wine using supported liquid membrane extraction and Ag-capped silicon nanopillar SERS substrates. (July 2020) - Rostami, Simindokht; Zór, Kinga; Zhai, Demi Shuang; Viehrig, Marlitt; Morelli, Lidia; Mehdinia, Ali; Smedsgaard, Jørn; Rindzevicius, Tomas; Boisen, Anja
Abstract: Mycotoxins are toxic secondary metabolites produced by fungi, found in a variety of food sources and cause diseases and death in both humans and animals. On-site and easy to use detection would be significant improvement considering the currently used methods. We present an approach, based on surface-enhanced Raman spectroscopy (SERS), where label-free detection of Ochratoxin A (OTA) was achieved in a multiwell SERS detection platform. When quantifying OTA in wine samples the SERS-based detection was used in combination with high throughput supported liquid membrane (SLM) extraction. The obtained detection limit in white wine was 115 ppb and we found that the SERS-based quantification is comparable with LC-MS. However, we also found that the matrix effect from red wine was interfering with both SERS and LC-MS detection. The SLM-SERS method provides a time and cost effective approach for OTA detection, which is a clear advantage over other extraction and direct detection approaches. Graphical abstract: Image 1 Highlights: Direct, label-free detection of Ochratoxin A was achived on Ag nanopillar substate. Supported liquid membrane extraction was used for the extraction of Ochratoxin A. High throughput extraction was combined with SERS detection in multiwell platform. The SERS data from wine sample was comparable with LC-MS results based on R 2 values. The method is an important step towards cost efficient detection of Ochratoxin A.